Collaborative School Leadership Practices in Educational Partnerships to Support Deep Learning Implementation at SMAN 1 Muara Jawa - Hermin Susanti; Puguh Wahyu Prasetyo; Dian Hidayati (Vokatek: Jurnal Pengabdian Masyarakat, 2026)
Deep learning has become an important approach in educational transformation by promoting more reflective, collaborative, and contextual learning. Its implementation requires collaborative school leadership practices in educational partnerships to support meaningful learning. This study aims to analyse the principal's collaborative leadership practices in educational partnerships to support deep learning implementation at SMAN 1 Muara Jawa. This study employed a qualitative descriptive approach. The participants consisted of the principal, two vice principals, and two teachers selected through purposive sampling. Data were collected through semi-structured interviews, observation, and document analysis and analysed using the interactive analysis model of Miles, Huberman, and Saldaña. The findings indicate that the principal's collaborative leadership practices were reflected in human resource development, academic supervision, internal and external collaboration, and the participatory formulation of the school's vision and strategic direction. According to the participants' perspectives, these practices were perceived to support the implementation of deep learning through professional collaboration, stakeholder engagement, and providing opportunities for more reflective, collaborative, and contextual learning. These findings provide a contextual empirical illustration of collaborative school leadership practices in educational partnerships as they were perceived to support the implementation of deep learning within the context of SMAN 1 Muara Jawa.